Answer:
a = 1, b = 6
Explanation:
The equation given is as follows;
P(x) = a·x³ + b·x² + 3·x - 10
The above equation has a factor of x + 5, therefore, we have;
P(-5) = 0 = a·(-5)³ + b·(-5)² + 3·(-5) - 10
-125·a + 25·b + (-15) - 10 = 0
-125·a + 25·b - 25 = 0
-125·a + 25·b = 25...........(1)
Also, we are given that;
a·x³ + b·x² + 3·x - 10 divided by x + 1 as a remainder, R = -8, therefore;
P(-1) = -8 = a·(-1)³ + b·(-1)² + 3·(-1) - 10
-a + b - 13 = -8
-a + b = -8 + 13 = 5
-a + b = 5............................(2)
Multiply equation (2) by 25 and subtract from (1) gives
-125·a + 25·b - 25(-a + b) = 25 - 25×5
-100·a = 25 - 125 = -100
a = 1
Therefore, from equation (2) we have;
-1 + b = 5
b = 5 + 1 = 6.